2019
DOI: 10.14393/bj-v35n2a20198-41475
|View full text |Cite
|
Sign up to set email alerts
|

Direct in vitro regeneration of castor bean plants (Ricinus communis) using epicotyls

Abstract: DIRECT in vitro REGENERATION OF CASTOR BEAN PLANTS (Ricinus communis) USING EPICOTYLS REGENERAÇÃO DIRETA in-vitro DE PLANTAS DE MAMONA (Ricinus communis) USANDO EPICÓTILOSABSTRACT: A regeneration protocol for castor bean plant (Ricinus communis) was successfully developed using epicotyl sections obtained from in vitro seedlings. The maximum number of induced shoots (4.3 shoots/explant) and highest shoots frequency (75,56%) was obtained in WPM medium supplemented with TDZ (1 mg/L) and zeatin (0.5 mg/L), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Gil-Correal et al achieved a 75.56% frequency of regeneration and 4.3 shoots per explant by culturing epicotyls of the "VERC-02" genotype on a medium containing 1 mg/L of TDZ + 0.5 mg/L of zeatin. On the other hand, the 1 mg/L of TDZ + 0.5 mg/L of 6-BAP combination resulted in a large decrease in the regeneration frequency (37.78%) and number of shoots per explant (0.8) [48]. Studying a castor bean genotype from the Rajshahi University Botanical Garden, Alam et al found an 85% regeneration frequency for a culture medium with 3 mg/L of 6-BAP and 36% by using 4 mg/L of 6-BAP + 0.5 mg/L of NAA [45].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Gil-Correal et al achieved a 75.56% frequency of regeneration and 4.3 shoots per explant by culturing epicotyls of the "VERC-02" genotype on a medium containing 1 mg/L of TDZ + 0.5 mg/L of zeatin. On the other hand, the 1 mg/L of TDZ + 0.5 mg/L of 6-BAP combination resulted in a large decrease in the regeneration frequency (37.78%) and number of shoots per explant (0.8) [48]. Studying a castor bean genotype from the Rajshahi University Botanical Garden, Alam et al found an 85% regeneration frequency for a culture medium with 3 mg/L of 6-BAP and 36% by using 4 mg/L of 6-BAP + 0.5 mg/L of NAA [45].…”
Section: Discussionmentioning
confidence: 97%
“…The start of callus formation was observed at days 5-7, which corroborates the results of some other authors. Gill-Correal et al observed the emergence of a callus in the epicotyls of the "VERC-02" castor bean genotype on day 8 [48]. Rahman and Bari described a callus starting in the hypocotyls of cv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several scientific reports have focused on regeneration from hypocotyls and epicotyls in the Euphorbiaceae family [ 5 , 6 ], despite high recalcitrance. Regarding sacha inchi specifically, a few studies have reported the use of in vitro propagation to evaluate the auxin:cytokinin ratio in apical meristems [ 7 ] and different segments of the epicotyl and hypocotyl [ 8 – 10 ], with highest shooting but low process efficiency with 0.5 and 1 mg/L 6-benzylaminopurine and 0.1 mg/L and 0.25 mg/L 1-naphthylacetic acid (NAA).…”
Section: Introductionmentioning
confidence: 99%